Comparative Seismic Assessment of Ancient Masonry Churches - D'Amato, Michele; Gigliotti, Rosario; Laguardia, Raffaele (Frontiers in Built Environment, 2019)
The seismic risk assessment of the historical and architectural heritage is, nowadays, a very relevant topic due the potential human and economic losses involved in case of global or partial collapse. In order to preserve the inestimable value of such heritage, the prevention and mitigation of the seismic risk is needed and it cannot be postponed. Among the several methods available in the literature to perform vulnerability assessment on cultural heritage, this study focuses on two simplified methods proposed by the current Italian Directive containing the guide lines for assessment and reduction of cultural heritage seismic risk. Furthermore, a new simplified method is applied, capable at a territorial scale of quickly ranking the seismic behavior of ancient churches. In the paper, the considered evaluation methods are applied to the case study of the Matera Cathedral, named SS. Maria della Bruna. Then, the obtained results are compared with others of similar ancient churches, all belonging to the historical centre ‘Sassi of Matera’, a site protected by UNESCO having a moderate seismic hazard.